Face‐to‐Face Growth of Wafer‐Scale 2D Semiconducting MOF Films on Dielectric Substrates. Issue 13 (17th February 2021) - Liu, Youxing; Wei, Yanan; Liu, Minghui; Bai, Yichao; Wang, Xinyu; Shang, Shengcong; Du, Changsheng; Gao, Wenqiang; Chen, Jianyi; Liu, Yunqi
Abstract: The preparation of large‐area 2D conductive metal–organic framework (MOF) films remains highly desirable but challenging. Here, inspired by the capillary phenomenon, a face‐to‐face confinement growth method to grow conductive 2D Cu2 (TCPP) (TCPP = meso‐tetra(4‐carboxyphenyl)porphine) MOF films on dielectric substrates is developed. Trace amounts of solutions containing low‐concentration Cu 2+ and TCPP are pumped cyclically into a micropore interface to produce this growth. The crystal structures are confirmed with various characterization techniques, which include high‐resolution atomic force microscopy and cryogenic transmission electron microscopy (Cryo‐TEM). The Cu2 (TCPP) MOF film exhibit an electrical conductivity of ≈0.007 S cm −1, which is approximately four orders of magnitude higher than other carboxylic‐acid‐based MOF materials (10 −6 S cm −1 ). Other wafer‐scale conductive MOF films such as M3 (HHTP)2 (M = Cu, Co, and Ni; HHTP = 2, 3, 6, 7, 10, 11‐triphenylenehexol) can be produced utilizing this strategy and suggests this method has widescale applicability potential. Abstract : Inspired by the capillary phenomenon, a face‐to‐face confinement growth method is developed to grow high‐quality wafer‐sacle Cu2 (TCPP) (TCPP = meso‐tetra(4‐carboxyphenyl)porphine) metal–organic framework (MOF) film on dielectric substrates. The film exhibits p‐type semiconducting property and excellent photoelectric response. Meanwhile, this growth strategy can also be used to prepare other wafer‐sacle conductive MOF films.